The effect of dietary supplements on core temperature and sweating responses in hot environmental conditions: a meta-analysis and meta-regression - Jenny Peel (American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, 2025)
Dietary supplements are widely used among individuals exposed to hot environments, but whether their consumption confers any thermoregulatory effect is unclear. Therefore, we systematically evaluated the effect of dietary supplementation on key aspects of thermoregulation (core temperature [Tcore] and sweating responses) in the heat. Three databases were searched in April 2024. After screening, 124 peer-reviewed articles were identified for inclusion within three separate meta-analyses: (1) peak Tcore; (2) whole-body sweat rate (WBSR); (3) local sweat rate (LSR). The moderating effect of several variables (e.g. training and heat acclimation status), known to influence thermoregulatory function, were assessed via sub-analysis and meta-regression. There was no overall effect of the differing supplement types on WBSR (p = 0.405) and LSR (p = 0.769), despite taurine significantly increasing WBSR (n = 3, Hedges’ g = 0.79, p = 0.006). Peak Tcore was significantly affected by supplement type (p = 0.011), primarily due to caffeine’s small significant positive effect (n = 30; Hedges’ g = 0.44, p < 0.001) and taurine’s (n = 3, Hedges’ g = -0.66, p = 0.043) and oligonol’s (n = 3; Hedges’ g = -0.50, p = 0.014) medium significant negative effects. Dietary supplements, such as amino acids (e.g. taurine), some anti-oxidants and anti-inflammatories (e.g. oligonol) conferred the greatest thermoregulatory benefits during heat exposure. Taurine ingestion in such conditions may lower heat strain, which is likely through its augmentation of thermal sweating. Conversely, caffeine intake may potentially pose the greatest risk in the heat due to its effect on Tcore.